Kaposi sarcoma at the base of the tongue in a renal transplant patient. Issue 3 (7th March 2023) - Safia, Alaa; Farhat, Raed; Avraham, Yaniv; Merchavy, Shlomo
Abstract : Oral Kaposi Sarcoma (OKS) commonly occurs in patients with AIDS. The incidence of Kaposi sarcoma (KS) is greatly increased in renal transplant recipients compared with the general population, with particular prevalence in certain ethnic groups where it can occur in up to 5% of transplant recipients. From them, only 2% can manifest first with OKS. A man in his early 40s, 2 years after kidney transplantation, presented with a reddish-purple hypertrophic ulcerated lesion at the base of the tongue. Cervical ultrasonography revealed enlarged lymph nodes, and pathological examination of biopsies revealed KS. The patient had HIV-negative status. Following an investigation, calcineurin inhibitor treatment was stopped, and an mTOR (mammalian target of rapamycin) inhibitor treatment was started. Fibreoptic examination 3 months after beginning mTOR inhibitor treatment revealed no traces of the disease in the base of the tongue. An isolated oral lesion should not distract clinicians from further systemic investigation for metastatic disease. OKS is a rare but serious complication in kidney transplant patients after receiving calcineurin inhibitor that could result in airway obstruction due to mass effect or bleeding and aspiration. Early diagnosis and management of OKS in a renal transplant patient who received a calcineurin inhibitor carry a good prognosis. OKS can be managed by changing the treatment regime to an mTOR inhibitor followed by radiation therapy. This contrasts with KS treatment in non-renal transplant patients without calcineurin inhibitors who may need treatment using different modalities such as surgery and chemotherapy. We emphasise the importance of this case for nephrologists responsible for patient follow-up after renal transplantation who prescribed calcineurin inhibitors. These patients must be advised that if they feel any physical mass in the tongue, they should immediately seek an examination by an ear, nose and throat specialist. Nephrologists and patients should be aware that these symptoms should not be underestimated.